Empowering the Traditional Pottery Entrepreneur Community through the Use of Technology to Maximize Business Income in Indonesia - Jenny Nancy Kaligis (International Assulta of Research and Engagement (IARE), 2023)
The aim of carrying out this community service activity is to provide an understanding of "Implementation of Digital Marketing for Pottery Entrepreneurs in Pulutan Remboken" which is located in Pulutan - Remboken - North Sulawesi. After carrying out this activity, it is hoped that it can increase understanding and benefits to the Tataaran Dua sub-district community. This community service activity is held within 1 (one) day. In carrying out this service activity, the problem found was that the public still did not have a good understanding of "Implementation of Digital Marketing for Pottery Entrepreneurs", in accordance with the principles of management functions and strategy. The results of community service activities show that there has been increased knowledge and understanding among the community to start running their businesses in facing the current digital era. Overall, community service activities received a positive response from Pulutan pottery entrepreneurs.